Diffractive swimming: Learning though a Robben Island crossing - Stevens, Marion (Critical Studies in Teaching and Learning, 2023)
This is an experimental piece following 30 years of implementation work in sexual and reproductive justice. In 2021, I started my PhD and wild water swimming. While separate initiatives, my time in the sea enabled deep, slow, focused diffractive process in which my thoughts, connections, obstacles, engagements, relationships, memories, and writing flowed with the human embodiment of ocean watery swimming. After my proposal was finalised, I ventured further, wanting to spend time swimming distances. I joined a group training to do a Robben Island crossing. This paper documents the slow journey of my mind and body in regular practice and process. I remember some who have passed on known and unknown as Robben Island evokes ideas of individual and collective struggle. On the day of the crossing, it was clear then cloudy and rough. I was left with mist and turbulence and yet, I came to shore and my PhD continues.